Analysis of Economic Convergence of Districts and Cities in North Sulawesi Province - Adawiah, Robiatul (Jurnal Ilmu Ekonomi JIE, 2024)
This research examines the previous year's Per Capita GRDP, Domestic Investment, Labor Force Participation Level, and Regency and City Open Unemployment Rates in North Sulawesi. The methodology is quantitative and obtained from the Central Statistics Agency, covering fifteen districts and cities in North Sulawesi from 2017-2022. This research uses a panel data regression analysis method using the Fixed Effect Model approach to determine the occurrence of absolute convergence and the Random Effect Model of conditional convergence. The findings of this research show that the GDP Per Capita variable in the previous year had a significant positive value, Domestic Investors had a positive and insignificant value, the Labor Force Participation Rate had a negative and insignificant value, and the Open Unemployment Rate had a negative and insignificant value.